2021
DOI: 10.1016/j.heliyon.2021.e06377
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, dissipation behavior and dietary risk assessment of a combi-product of chlorantraniliprole and λ-cyhalothrin in/on pigeonpea (Cajanus cajan L.)

Abstract: Pigeonpea ( Cajanus cajan L.) is an annually cultivated food and forage crop, attacked by a large number of pests mainly pod borer ( Helicoverpa armigera ). For the control of this insect pest, a combination of broad-spectrum insecticides viz., chlorantraniliprole and λ-cyhalothrin have been in use to reduce the pod damage and increase crop production worldwide. Therefore, a field trial was conducted to study dissipation and persistence behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The various concentrations (especially in the linear dynamic range) were recorded to determine the analytical method's limit of detection (LOD) and limit of quantitation (LOQ). The recovery of phytohormones was used to assess the accuracy and precision ( Kansara et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The various concentrations (especially in the linear dynamic range) were recorded to determine the analytical method's limit of detection (LOD) and limit of quantitation (LOQ). The recovery of phytohormones was used to assess the accuracy and precision ( Kansara et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that chlorantraniliprole persisted up to 30 days at RD and 2RD with the half-lives (t1/2) of chlorantraniliprole ranged from 4.95 to 5.78 days at RD and 2RD in pigeonpea, respectively. Residues of the insecticide were below LOQ when measured from the soil on the 30th day [29].…”
Section: Residue Of Diamide In/on Food Samplesmentioning
confidence: 89%
“…RQ was estimated for the residues determined directly on the treated pigeonpea plants sprayed with an insecticide containing a combination from chlorantraniliprole and λ-cyhalothrin at 30 and 60 g a.i. ha -1 [29]. Their results indicated that dietary risk assessment (RQ <1), which suggested that the application of the combination at RD is safe for the consumers.…”
Section: Dietary Risk Assessment Of Diamide Insecticidesmentioning
confidence: 96%
See 1 more Smart Citation
“…The lowest addition level of the analysis method was designated as the limit of quantification (LOQ) of both bacopasides and bacoside throughout the experiment, and the limit of detection (LOD) was estimated as three times the signal-to-noise ratio (S/N). For LOD and LOQ calculation of all three compounds were calculated by using the following formulas: (a) LOD (µg/kg) = (mean of standard deviation/Slope) × 3; (b) LOQ (µg/kg) = (mean of standard deviation/Slope) × 10 [11,12]. A recovery study was used to assess the accuracy and precision.…”
Section: Analytical Methods Validationmentioning
confidence: 99%